Contiguous haemangioblastomas of the brain and spine in a patient of Von Hippel-Lindau disease - Rahman, Asifur (BMJ Publishing Group, 2013)
Von Hippel-Lindau (VHL) disease is an inherited, autosomal-dominant syndrome caused by heterozygous germline mutations in the VHL gene, and predisposing to the development of benign and malignant tumours and cysts in multiple organ systems involving eyes, kidneys, pancreas, liver and central nervous system. The responsible tumour suppressor gene for VHL disease is in chromosome 3p25. We are presenting a case of a patient with both cerebellar as well as spinal haemangioblastoma in addition to polycystic pancreas. We operated on both the spinal and the cerebellar haemangioblastomas and the patient had made a very good recovery. We present this case for its rarity along with the literature review.